Sticky Inflation and the Real Effects of Exchange Rate Based Stabilization - Celasun, Oya (IMF Working Papers; Working Paper ;, 2003)
Exchange rate-based inflation stabilization (ERBS) policies are associated with a boom-recession cycle in economic activity and sustained real exchange rate appreciation. A class of models in the literature has explained these empirical regularities with the lack of credibility of the stabilization plans. The lack-of-credibility models typically assume perfectly forward-looking pricing behavior without inflation stickiness and attribute the slow decline in inflation to the consumption boom that occurs due to the perceived temporariness of the ERBS policy. This paper tests the empirical validity of forward-looking pricing behavior in Mexico and Turkey, two countries which have experienced ERBS. It finds that the forward- and backward-looking components of inflation weigh approximately equally in pricing behavior, and therefore, that inflation is partially sticky. The paper then develops the theoretical implications of partial inflation stickiness in a lack of credibility model of ERBS and concludes that the presence of stickiness significantly reduces the persistence of the consumption boom predicted by the model, but helps to explain the recession in the late phase of the stabilization.